Hubungan Pelayanan Prima Terhadap Kepuasan Konsumen Pada UMKM Serba Cetak Jakarta Selatan - Kamelia Aziza; Nurhadi Nurhadi; Seno Sudarmono Hadi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to determine the service provided by employees of UMKM Serba Cetak towards consumer satisfaction after completing a purchase or order at UMKM Serba Cetak. The study covers in accordance with the Key Performance Indicators consisting of six divisions and analyzes the level of service towards consumer satisfaction. The research method used involves observation for one month at UMKM Serba Cetak and interviews as well as distributing questionnaires to consumers who have made orders at UMKM Serba Cetak, as well as market data analysis to identify the relationship between excellent service and consumer satisfaction at UMKM Serba Cetak. The sample in this study was the entire population of 15 people; the analysis and testing tools used were IBM SPP Version 21 and Microsoft Excel. The results of the study showed that the work in accordance with the Key Performance Indicators experienced significant changes at UMKM Serba Cetak, such as increased sales and income every month, financial data was well managed, and online promotions received good engagement. Based on the results of the validity test with a value of 0.5140, which was declared valid, and the results of the CSI analysis obtained were 86.90%, which were declared very satisfied.